Pengembangan media interaktif berbasis S.id berbantuan canva pada pembelajaran materi siklus air kelas V siswa sekolah dasar - Dina Rosyada (COLLASE (Creative of Learning Students Elementary Education), 2023)
This research is motivated by the learning outcomes of students in several elementary schools which are under the KKM, namely 70 in science subjects for class V water cycle material because interactive learning media have not been implemented according to the needs of students and teachers in the current era. This research is a type of qualitative and quantitative research with research and development design R&D (Research and Development). The result is that teachers want the development of S.id-based interactive media with the help of Canva. This s.id-based interactive media product is in the form of a modified link with the Canva application containing water cycle material, videos, songs, and educational games. The results of the validation from media experts, material experts, and practitioners each obtained a score of 88.50; 91.50; and 92.00 with the category of â€œvery decentâ€. The results of student responses were 87.33% and responses from teachers in three elementary schools with an average of 91.11% with the product category "very feasible". Based on these results, it is concluded that the development of interactive media based on s.id assisted by Canva has proven to be as needed, very feasible to use.